An Analysis of Taboo Words in Megan Thee Stallion’s Song Lyrics on Album “Fever” - Sinaga, Amelia Putrilanel; Siregar, Florence; Pasaribu, Sastha Theresia; Rangkuti, Rahmadsyah (Universitas Negeri Padang, 2023)
This article aimed to talk about taboo words in the song lyrics on Megan Thee Stallion's